Errors in Diagnostic Test Use and Interpretation Contribute to the High Number of Lyme Disease Referrals in a Low-Incidence State. (11th January 2020) - Boyce, Ross M; Speight, Carly; Lin, Jessica T; Farel, Claire E
Abstract: Lyme disease accounted for more than two-thirds (56 of 81, 69.1%) of all tick-borne disease referrals to a large, academic infectious diseases clinic in a low-incidence state. Deviations from diagnostic testing guidelines and errors in test interpretation were common (23 of 35, 65.7%), suggesting that frontline providers need additional clinical support.